D’Annunzio fruitore di musica a Venezia - Uras, Lara Sonja (Archivio d’Annunzio, 2015)
Through an examination of the correspondence, published and unpublished, the comparison of the press of the time with the biography and literary production of d’Annunzio, it is possible to know which music he listened to and comprehend his relationships with important musicians during his stays in Venice. This overview of sources can offer useful elements to understand musical references present in the literary works of d’Annunzio. In Venice, early music sacred and profane coexists - like a counterpoint - with contemporary and folk music, the sounds of war combined with the city’s sounds and silence. In Venice there are plenty of organists and organ music; the city gets «resonant like a huge organ», as the musical instrument described in the manuscript entitled Chiomazzurra, conserved by the poet and signed R. Bossi: an «arciorgano» with seven thousand glass pipes reminiscent of the fable told in Il fuoco. The organ becomes the favorite musical instrument, prevails like a basso ostinato in the poet’s life, conducts a «thematic function» in his literary ‘polyphony’ to become, sometimes, ‘leitmotif’ in his train of thoughts.